Gestión de conocimientos en el desempeño de los docentes de la facultad de ciencias económicas y de negocios de la Universidad Nacional de la Amazonía Peruana 2022 - Burga Pérez, David Eduardo (2023)
The present investigation had as a general objective to determine the relationship between knowledge management and the performance of teachers of the Faculty of Economics and Business of the National University of the Peruvian Amazon 2022; used the quantitative method, correlational level, for which it took a sample of 37 teachers, who were surveyed through a questionnaire. The results are: The professors of the faculty have received training opportunities, 65.63% once, and 28.13%, many times. These offers generated a lot of interest, 66.67%. The teachers who were interested, if they participated in the training, 89.66%. The institution presents weakness due to lack of incentives in academic mobility, 78.13% never received this possibility, and sometime, 15.63%. Those who received, 85.71%, felt regular interest, explained by the little anticipation or they were not topics of interest. Of those who expressed interest, 71.43% participated. It is important to achieve greater knowledge, with the consequent impact on the teacher's teaching performance, 62.50% explained that they have a regular interest in doing so, and 34.35% had a lot of interest. There is a problem, 59.38% have a regular command of the teaching materials. In terms of teaching in pedagogy, 78.13% have regular proficiency. Teachers show regular interest in knowing research methods, 65.63%; the time they dedicate is scarce, and their university work has little connection with research. They have a regular mastery of research subjects, 84.38%. The commitment is reduced to develop research projects, 62.50%.